Coomperation: Sustainable migration management model based on respect for Human Rights - Galiana Marina, Fernando (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2024)
The quasi-omnipresence of the migration phenomenon in the media during the last decade has transformed the immigration discourse, generating changes in migratory perception, legislation and policy. Research on this matter promotes migration management from a paradigm of coomperation, understood as a sustainable model benefitting all actors involved, while contributing to the achievement of a common objective from an approach based on respect for human rights and their jurisdictional guarantees. From this model, the article proposes to consider the opportunity that migratory flows offer to revitalize the economy, promote entrepreneurship and contribute to the sustainability of the European welfare state.
Keywords: immigration management, human rights, coomperation, European Union.